The Past Time Uses of the Imperfect in the Aramaic of Daniel - Carver, Daniel E (Aramaic studies, 2021)
In the Aramaic of Daniel, the imperfect expresses past situations 29 times. Scholars have long wrestled with these past time uses, and although important contributions have been made along the way, one of the most salient semantic issues that arise with these uses—the semantic intersection of imperfective aspect and telicity—has been overlooked. This study addresses this issue directly by providing a linguistic analysis of the past imperfective uses of the imperfect that describes their semantics in light of situation aspect and (un)boundedness. This study also describes the past modal use of the imperfect, and offers a linguistic explanation for how the imperfect acquired such a use. Ultimately, this study provides a linguistic analysis of the past time uses of the imperfect that fosters more artful and nuanced readings of the text in light of its semantic and functional sophistication.